PENGARUH KEMUDAHAN PENGGUNAAN TERHADAP SIKAP PENGGUNAAN PADA PHOTOBOX DI MARSKOPI BANDA ACEH - Edinda Puteri Qurata Ayyuna; A. Razak; Asmaul Husna; Achmad Mustofa; Amrusi Amrusi (REKOGNISI : Jurnal Pendidikan dan Kependidikan (E-ISSN 2599-2260), 2026)
The development of digital service technology is currently growing rapidly. Photobox is one of the self-service technologies that are highly popular, especially among young people. Perceived ease of use is one of the important factors that can influence users’ attitudes in accepting and using a technology. This study aims to determine the effect of perceived ease of use on usage attitude toward photobox services at Marskopi Banda Aceh. This study employed a quantitative approach. The population in this study consisted of customers who had used photobox services at Marskopi Banda Aceh, with the sampling technique using accidental sampling involving 60 respondents. Data collection techniques used were questionnaires and documentation. The data analysis techniques used included descriptive statistical analysis, normality test, and simple linear regression analysis. The results of the study indicate that perceived ease of use has a positive and significant effect on the usage attitude toward photobox services at Marskopi Banda Aceh. The simple linear regression analysis produced the equation Y = 17.766 + 0.527X. The regression coefficient of the perceived ease of use variable was 0.527, indicating that every increase in the perceived ease of use variable would improve customers’ usage attitudes toward photobox services. Furthermore, the results of the t-test at a significance level of 0.05 showed that the t-count value of 6.706 was greater than the t-table value of 2.001 (6.706 > 2.001), meaning that the perceived ease of use variable had a positive effect on usage attitude, with Ha accepted and Ho rejected. The coefficient of determination (r²) of 43.7% indicates that perceived ease of use influences the usage attitude toward photobox services at Marskopi Banda Aceh, while the remaining 56.3% is influenced by other variables not examined in this study, such as perceived usefulness, trust, and system quality. Based on these findings, it can be concluded that perceived ease of use plays an important role in shaping users’ attitudes toward photobox services at Marskopi Banda Aceh.